Lepidoptera recorded on snow in Central Poland - Soszyńska-Maj, Agnieszka; Buszko, Jarosław (Entomologica Fennica, 2011)
Sixteen species of Lepidoptera, belonging to 10 families, were recorded on snow in Central Poland. Two episodes of mass occurrence on snow were observed: adults of Operophtera brumata and larvae of Euthrix potatoria. Twelve species were recorded from snow for the first time in general. Three ecological groups of snow active Lepidoptera were distinguished: 1) autumn and winter active moths, 2) overwintering species which could be periodically activated from diapause, and 3) early spring active species. The ecology of winter active Lepidoptera is discussed. All were classified as chionoxenes, while O. brumata was considered as the moth most regularly recorded on snow andmost likely to be met in winter.